Mental Well-Being of Single Mothers: The Role of Coping Orientation and Social Support (Jagannath University Journal of Life and Earth Sciences, 2025)
The primary goal of this study was to explore the relationship between coping mechanisms and the extent of social support to the mental well-being of single mothers. Additionally, the research investigated how demographic variables relate to this dependent construct. An adapted Bangla version of the measuring tool was employed i.e., coping orientation(Zaman and Liza, 2024), social support (Shimul, 2007), andmental well-being scale(Zaman and Liza, 2024)  to collect data from a sample of 250 single mothers (92 divorced, 55 separated, and 103 widowed) selected purposively from various places social organizations, parenting groups, or even through mutual friends in Dhaka city. Results suggested that coping orientation and social support were significantly and positively correlated with mental well-being. The findings on social support indicated that two key predictors-friends and significant others collectively accounted for 12.8% of the variance in mental well-being. Among these, friends emerged as the most influential predictor, explaining 9.9% of the variance on its own. Additionally, the analysis of coping orientation and mental well-being showed that two significant predictors, emotion-focused and problem-focused coping, together accounted for 23.1% of the variance. Emotion-focused coping was the strongest predictor, explaining 16% of the variance on its own. The joint effect revealed that the four significant predictors explained jointly 30.8% of the variance, and the strongest predictor of mental well-being was emotion-focused, which alone explained 16% of the variance. The results identified five significant predictors that collectively explained 36.9% of the variance, with emotion being the strongest predictor, accounting for 16% of the variance on its own. The findings also revealed a significant relationship between demographic factors such as age, marital status, education, and the number of children and mental well-being. The study underscores the importance of coping orientation and social support in enhancing the mental well-being of single mothers.Jagannath University Journal of Life and Earth Sciences, 10 (2): 178-194 (December 2024)